Hubungan Mutu Pelayanan Kesehatanm Dengan Kepuasan Pasien Di Upt Puskesmas Bestari Kota Medan Tahun 2024 - Elvi Andriany Simbolon; Kesaktian Manurung; Janno Sinaga; Donal Nababan; Frida Lina Tarigan (Journal of Pharmaceutical and Sciences, 2026)
Health is one of the basic needs of society which is very important in supporting daily activities. As people's living standards increase, so do people's needs, hopes and demands for quality health. This situation requires health service providers such as hospitals to improve the quality of services better and provide satisfaction for consumers as users of health services. The problem formulation in this research is "Evaluation of the Relationship between Health Service Quality and Patient Satisfaction at UPT. Puskesmas Bestari, Medan City in 2024." The general objective of this research is to evaluate the relationship between the quality of health services and patient satisfaction. This type of research is observational analytics with a crosssectional design, namely research to study the dynamics of the correlation between risk factors and effects, using an approach, observational method, or data collection. This research was carried out from October 2024 to February 2025. The samples in this study were patients who came for treatment at UPT. Puskesmas Bestari in Medan City and received health services for 96 people. the majority of respondents in this study were in the age range of 36 - 40 years, 35.4%. The majority of respondents were women, namely 58.3%. Based on education level, the majority of respondents had a high school/equivalent education, 51.0%. Meanwhile, from the work aspect, the majority of respondents worked as employees or laborers with a total of 47.9%. Respondents who were satisfied were 66.7%, while respondents who were dissatisfied were 33.3%. Based on the results of research conducted at UPT Puskesmas Bestari, it can be concluded that: There is a relationship between the quality of health services from the dimension of responsiveness and patient satisfaction. There is a relationship between the quality of health services from the quality assurance dimension and patient satisfaction. There is a relationship between the quality of health services from the tangible facilities and patient satisfaction dimensions. There is a relationship between the quality of health services from the dimension of concern (empathy) and patient satisfaction. There is a relationship between the quality of health services from the reliability dimension and patient satisfaction at UPT. Puskesmas Bestari, Medan City in 2024